RETRACTED (ditarik) : PENERAPAN SOFTWARE AKUNTANSI ONLINE SEBAGAI PENUNJANG PENCATATAN LAPORAN KEUANGAN - Rahardja, Untung; Aini, Qurotul; Hardini, Marviola (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
RETRACTED (ditarik) Following a rigorous, carefully concerns and communication between the publisher and the authors of the article published in Positif : Jurnal Sistem dan Teknologi Informasi to article entitled â€œPENERAPAN SOFTWARE AKUNTANSI ONLINE SEBAGAI PENUNJANG PENCATATAN LAPORAN KEUANGANâ€ Vol 4, No 2, pp. 78-87, November 2018. This paper has been withdrawn at the request of the author and has been retracted. The article contained redundant material, the author has informed editor that the paper was published in SISFOTENIKA, 8(2), pp.176-187. The publisher apologizes to the authors and readers for the error and any inconvenience caused.